Investigation of the Effect of High Temperature on the Microstructure of Conventional Concrete Containing High Grade of Portland Cement (Journal of Civil Engineering Researchers, 2025)
In this laboratory study, a mixed concrete design containing 500 kg/m3 Portland cement was prepared, and elastic modulus testing, X-ray diffraction (XRD) analysis, and scanning electron microscope (SEM) image analysis were performed on concrete samples at 21 and 600 °C after a curing age of 90 days to investigate and evaluate the microstructure of concrete at room temperature and under high temperature. The results of the tests indicate that high temperature causes a decrease in the results, so that the elastic modulus of concrete experienced a decrease of 71.63% from 73.33 GPa at 21°C to 24.12 GPa at 600 °C, and in the XRD analysis, a decrease in the height of the peaks of hydrated elements is observed. The low peak height of calcium hydroxide in the XRD spectrum indicates a proper polymerization process in conventional concrete. In SEM analysis, at a temperature of 21 °C, due to the completion of a large part of the polymerization process, the tree structure, pores and unhydrated particles are seen in their minimum amount, but after applying a temperature of 600 °C to the concrete sample, with damage to the microstructure of the concrete and the hydrated calcium aluminum sulfate (C-A-S-H) and hydrated calcium silicate (C-S-H) gels, an increase in the tree structure, pores and cracks is evident in the concrete sample.
Keywords: Ordinary Concrete; Heat; Modulus of Elasticity; Hydrated Calcium Silicate (C-S-H); Calcium Hydroxide (Ca(OH)2)